2021
DOI: 10.2147/dddt.s300376
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal Circ-XIAP Promotes Docetaxel Resistance in Prostate Cancer by Regulating miR-1182/TPD52 Axis

Abstract: Background Exosomal circular RNAs (circRNAs) are involved in the pathogenesis of prostate cancer (PCa) and chemotherapy resistance. This research aimed to explore the function and molecular mechanism of circRNA X-linked inhibitor of apoptosis (circ-XIAP) in docetaxel (DTX) resistance of PCa. Methods The expression of circ-XIAP, microRNA-1182 (miR-1182), tumor protein D52 (TPD52) was measured by quantitative real-time polymerase chain reaction (qRT-PCR). Exosomes were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…In addition, suppressing hsa_circ_0000735 promoted docetaxel sensitivity and suppressed tumor growth in vivo . Zhang et al reported that exosomal circ-XIAP promoted docetaxel resistance in PCa by altering miR-1182/TPD52 axis (Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, suppressing hsa_circ_0000735 promoted docetaxel sensitivity and suppressed tumor growth in vivo . Zhang et al reported that exosomal circ-XIAP promoted docetaxel resistance in PCa by altering miR-1182/TPD52 axis (Zhang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this study did not investigate whether exosomal circRNAs could be taken up by cells and function. Zhang et al discovered that circ-XIAP was up-regulated in exosomes from docetaxel-resistant cell lines and could be transmitted via exosomes (Zhang et al, 2021 ). Adding exosomes from docetaxel-resistant cells increased circ-XIAP level in prostate cancer cell lines, suggesting that exosomes containing circ-XIAP could be absorbed.…”
Section: Resultsmentioning
confidence: 99%
“…Specific delivery of chemotherapeutic agents to the tumor cells can be improved with exosome or nanoparticle conjugations. For instance, exosome-mediated transfer of apoptosis inducers such as circRNA and miRNA may help overcome chemotherapy resistance (91,136). Cancerspecific, pro-apoptotic drug-drug conjugate for SMAC and doxorubicin suppressed tumor growth in drug-resistant lung cancer model (137).…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of exosomal circular RNA of XIAP (Circ-XIAP) to the docetaxel-resistant prostate cancer cells acted as a miRNA sponge for miR-1182 and promoted resistance (91). A recent report showed that anti-apoptotic proteins FLICE-like inhibitory protein (FLIP) and XIAP are downregulated after hydrogen peroxide in the imatinib-resistant CML cells (92).…”
Section: Targeting the Inhibitors Of Apoptosismentioning
confidence: 99%
“…Exo-circRNAs have also demonstrated to function in drug resistance regulation through miRNA sponging. For instance, exosomal circ_0072083 promoted TMZ resistance via increasing Nanoghomeobox (NANOG) and administering miR-1252-5p mediated degradation and demethylation in glioma ( Ding C. Y. et al, 2021 ) and additionally exosomal circ-XIAP stimulated DTX resistance of PC through the regulation of miR-1182/TPD52 axis further providing a promising therapeutic mark for PC chemotherapy ( Zhang et al, 2021 ). In another study, exosomal mmu_circ_0000250 modified adipose derived mesynchymal stem cells advanced wound healing in diabetic mice by inducing miR-128-3p/SIRT1 mediated autophagy ( Shi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%